2016
DOI: 10.1016/j.exger.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Moderately lower temperatures greatly extend the lifespan of Brachionus manjavacas (Rotifera): Thermodynamics or gene regulation?

Abstract: Environmental temperature greatly affects lifespan in a wide variety of animals, but the exact mechanisms underlying this effect are still largely unknown. A moderate temperature decrease from 22°C to 16°C extends the lifespan of the monogonont rotifer Brachionus manjavacas by up to 163%. Thermodynamic effects on metabolism contribute to this increase in longevity, but are not the only cause. When rotifers are exposed to 16°C for four days and then transfered to 22°C, they survive until day 13 at nearly identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…This possibility may be more likely in temperate than in tropical or polar regions. Lifespan in some rotifers is extended by low temperature (Halbach, ; Johnston & Snell, ; Snell, ; Snell & King, ), dietary restriction (Gribble & Mark Welch, ; Halbach & Halbach‐Keup, ; Kirk, ; Weithoff, ), and hypoxia (Snell, Johnston, & Jones, ). The study by Johnston & Snell on the effect of temperature on survival, reproduction, and stress tolerance in B. manjavaca s ( B. plicatilis species complex) is particularly instructive.…”
Section: Sex In Natural Populationsmentioning
confidence: 99%
“…This possibility may be more likely in temperate than in tropical or polar regions. Lifespan in some rotifers is extended by low temperature (Halbach, ; Johnston & Snell, ; Snell, ; Snell & King, ), dietary restriction (Gribble & Mark Welch, ; Halbach & Halbach‐Keup, ; Kirk, ; Weithoff, ), and hypoxia (Snell, Johnston, & Jones, ). The study by Johnston & Snell on the effect of temperature on survival, reproduction, and stress tolerance in B. manjavaca s ( B. plicatilis species complex) is particularly instructive.…”
Section: Sex In Natural Populationsmentioning
confidence: 99%
“…Their different responses to temperature manipulation might be expected, as there seems to be a link between nutrient and thermal sensing, metabolism, and longevity (Horikawa et al., ). Recently, Johnston and Snell () observed that lifespans of closely related rotifer species respond differently to temperature manipulation. Even more closely, Henning‐Lucass, Cordellier, Streit, and Schwenk (), studying the response to temperature in Daphnia galeata clones of different age (i.e., hatched from resting eggs of different age), found no overall effect of temperature on Daphnia survival rate, as individuals from clones of different age reacted differently.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature effect on lifespan is not merely a passive process, but is under gene regulation (Johnston & Snell, 2016;Keil et al, 2015;Xiao et al, 2013). Hence, intraspecific differences in how genotypes and phenotypes, here sexes, respond in lifespan to temperature change are very much expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations